2021
DOI: 10.1016/j.celrep.2021.109676
|View full text |Cite
|
Sign up to set email alerts
|

Light regulates alternative splicing outcomes via the TOR kinase pathway

Abstract: Highlights d Chloroplast retrograde signals control alternative splicing in Arabidopsis thaliana d TOR kinase has a central role in alternative splicing control in roots d Mitochondria mediate light/sucrose effects on alternative splicing in roots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
(86 reference statements)
3
38
0
Order By: Relevance
“…This glycolysis-dependent promotion of TOR activity could be a specificity of heterotrophic tissues that allows a systemic integration of developmental progression with shoot photosynthetic capacity. Such coupling has been reported for the light-dependent regulation of alternative splicing in roots which is triggered by shoot-photosynthesized sugars and compromised when TOR levels are reduced or its activity reduced (Riegler et al , 2021).…”
Section: Resultsmentioning
confidence: 65%
“…This glycolysis-dependent promotion of TOR activity could be a specificity of heterotrophic tissues that allows a systemic integration of developmental progression with shoot photosynthetic capacity. Such coupling has been reported for the light-dependent regulation of alternative splicing in roots which is triggered by shoot-photosynthesized sugars and compromised when TOR levels are reduced or its activity reduced (Riegler et al , 2021).…”
Section: Resultsmentioning
confidence: 65%
“…Thus, effective retrograde communication and its linkages with RNA metabolism have been extensively studied [ 76 ]. For example, it was demonstrated that changes in the PQ redox pool may regulate the alternative splicing process [ 38 , 77 , 78 ]. Recently, the basis of these mechanisms was revealed, showing that light increases the PolII elongation rate, while in darkness, elongation is reduced, which is consistent with the kinetic coupling model also found in mammalian cells [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies uncovered extensive light-sensitive AS and APA programs in this plant. Of note, such rhythmic patterns were correlated with gene-level oscillations of factors involved in AS and APA [223,224]. More recently, it was shown that the TOR kinase, homolog of mammalian mTOR, modulates a specific splicing program in response to light.…”
Section: The Circadian Clock Pathway and Rna Processing Regulationmentioning
confidence: 95%